Robotics in underground coal mining: Enhancing efficiency and safety through technological innovation - Koul Parankush (Podzemni Radovi)
The aim of this paper is to explore how robotics can be applied to underground coal mining in order to make operations more efficient and safer with the help of technology. It calls for the use of regulations developed by industry bodies including the National Institute for Occupational Safety and Health (NIOSH) and the Mine Safety and Health Administration (MSHA) to ensure that robotics are used safely and efficiently in mining. The study also points to NIOSH efforts to resolve health and safety issues around automation technology in the mining industry. When high-tech robotic equipment is deployed, it demonstrates great productivity gains and less human suffering from disease. In demonstrating these innovations, the paper proposes that robotics must be continually innovated to maximize extraction of resources and worker safety, positioning robots as the new force in the coal mining industry.